Clusters, key clusters and local textual functions in Dickens - Mahlberg, Michaela (Edinburgh University Press, 2007)
The paper argues that corpus linguistics can make useful contributions to the descriptive inventory of literary stylistics. The concept of local textual functions is employed as a descriptive tool for the stylistic analysis of a corpus of texts by Charles Dickens. It is suggested that clusters, i.e. repeated sequences of words, can be interpreted as pointers to local textual functions. The focus is on five-word clusters and five functional groups are identified: Labels, Speech clusters, As If clusters, Body Part clusters and Time and Place clusters. The analysis draws on the identification of key clusters comparing the Dickens corpus with a corpus of nineteenth-century fiction, it identifies links to literary criticism and it gives specific attention to the group of Body Part clusters to illustrate the functional variation of clusters.